How to overcome the limitations of the Junior Alumni Program to increase Alumni POTEntial - Somodi, Klára (ICAReAlumni Conference Proceedings, 2023)
The Junior Alumni Program Framework •piloted in 2021/22 •volunteer based •extracurricular activity •a lumni powered (all presenters are alumni) •a ll activities are strictly professional •mirrors a typical medical student’s career path (pre clinical and clinical) • 80% of events are dedicated to self development oriented activities •20% to fun (motivational & professional cafés, career inn)